FAKTOR-FAKTOR YANG MEMPENGARUHI ORIENTASI KARIR INDIVIDU (SUATU TINJAUAN TEORITIS) - Harunnurrasyid Harunnurrasyid; Rahmi Widyanti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
Career management is an employee career management process that covers the stages of career planning activities, career development and counseling, and career decision making. Career management involves all parties including employees concerned with the unit where the employee works, and the organization as a whole. Therefore, career management covers a vast area of activity. In this paper the stages to be discussed are about the factors that affect the career orientation of individuals. Career management covers a vast area of activity. The importance of career management for employees is to increase the potential and productivity for their advancement, while for the company is to plan their human resources in improving the company's business value and business competition. Career planning and development is a career management function. companies that want their employees to work with good skills and knowledge should be able to plan and develop their employees' careers, while for employees with career planning and development, employees can know their career goals and direction.